Experimentation, questioning and the use of digital resources in the application of a didactic sequence for the teaching of solutions in high school (Research, Society and Development, 2020)
The present research, of qualitative nature, aimed at the elaboration, application and evaluation of a Didactic Sequence (SD) using the theme "Artificial juices". The aim was to assist Chemistry teachers in their theoretical and practical classes, emphasizing the importance of Experimentation in Teaching Chemistry during High School by bringing chemical concepts closer to the students' reality. The discussions about the content of Solutions were carried out through texts and alternative materials in the realization of chemical experiments. A classroom was opened on the Google Classroom platform to provide materials for study, dialogue with students and post the activities developed. The elaboration and application of the SD was based on the textbook adopted at the School, on books and articles selected in the Google Scholar search tool involving Investigative Teaching and Problematization. The Didactic Sequence was applied to a second-year high school class at a state public school in the state of Minas Gerais. Some technological resources and the investigative approach were used. The SD was didactically organized in the Three Pedagogical Moments proposed by Delizoicov et al. (2018). The application of SD lasted five classes of 50 minutes and involved 32 students. The results obtained showed that this approach stimulates student involvement, generates learning, favors the appropriation of scientific language, facilitates the perception of the relationships between chemical knowledge and manages to involve Science and its Technologies with Society and the students' Environment, including the practical aspects related to the contemporary world.